1996
DOI: 10.1210/jc.81.2.555
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in growth hormone-deficient adults: defects in glucose utilization and glycogen synthase activity

Abstract: Fourteen GH-deficient (GHD) adults were compared with 12 age-, sex-, and body mass index-matched control subjects using a baseline tritiated glucose equilibration period and euglycemic-hyperinsulinemic (approximately 55 mU/L) clamp in conjunction with paired muscle biopsies for measurement of glycogen synthase fractional velocity (FV0.1). Despite similar basal rates of total glucose disposal (Rd), there was a 64% reduction in the insulin-stimulated rise (delta) in Rd in the GHD adults compared to that in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 0 publications
4
61
2
2
Order By: Relevance
“…The fact that isolated GHD and GHD in combination with multiple pituitary deficiencies are both equally associated with the development of diabetes adds an indirect argument to the concept that GHD in adult-onset hypopituitarism by itself plays a not unimportant role in the development of the characteristic adverse metabolic profile, and therefore GH replacement may be regarded essential (28). The duration of GHD had no influence on the presence of diabetes, despite this determinant having previously been demonstrated to be the single most important predictor of insulin resistance in a study using the hyperinsulinemic normoglycemic clamp technique in a small group of patients (10). The advantages and drawbacks of large pharmacoepidemiological databases are now well recognized (13).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fact that isolated GHD and GHD in combination with multiple pituitary deficiencies are both equally associated with the development of diabetes adds an indirect argument to the concept that GHD in adult-onset hypopituitarism by itself plays a not unimportant role in the development of the characteristic adverse metabolic profile, and therefore GH replacement may be regarded essential (28). The duration of GHD had no influence on the presence of diabetes, despite this determinant having previously been demonstrated to be the single most important predictor of insulin resistance in a study using the hyperinsulinemic normoglycemic clamp technique in a small group of patients (10). The advantages and drawbacks of large pharmacoepidemiological databases are now well recognized (13).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the first clinical studies pointed toward an impaired carbohydrate metabolism, because an increased prevalence of impaired glucose tolerance was found in 14 out of 40 adult GHD patients (8). Furthermore, using the hyperinsulinemic normoglycemic clamp technique, a significant impairment of insulin sensitivity was observed (9,10). An increase in free fatty acids related to the tendency toward obesity and to the increase in visceral fat has been implicated in the insulin resistance, because reduction of the free fatty acids by the niacin derivative acipimox ameliorates GH secretion in obesity and in GHD (11).…”
Section: Introductionmentioning
confidence: 99%
“…In one of the most comprehensive studies of the metabolic consequences of GHD, Hew et al [9] showed that fat mass was clearly higher (31.1 vs. 25.5%) and insulin-stimulated glucose uptake severely impaired (30 vs. 55 µmol/kg·FFM·min) in 14 patients with GHD matched for age and body mass index (BMI) with 12 healthy controls. Similarly, when we compared 10 patients with GHD with 300 controls matched for BMI (27 kg/m 2 ), the patients with GHD again appeared to have 20% more fat (30.4 vs. 25%) than the controls (M. Bramnert, unpublished data).…”
Section: Metabolic Consequences Of Ghd In Adultsmentioning
confidence: 99%
“…During the past two decades, evidence has emerged linking hypopituitarism with cardiovascular risk factors, including hyperlipidaemia (11,12,13,14), visceral adiposity (15,16), insulin resistance (17) and vascular endothelial dysfunction (18,19,20).…”
Section: Introductionmentioning
confidence: 99%